2002
DOI: 10.1042/cs103s371s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a selective endothelin A receptor antagonist, ABT-627, in healthy normotensive anaesthetized rats developing acute pulmonary air embolism

Abstract: Acute pulmonary air embolism (APAE) injures the vascular endothelium in the lung and results in pulmonary hypertension (PH). Endothelins (ETs), a family of potent vasoactive peptides, are known to be associated with PH of various aetiologies. We evaluated the effects of ABT-627, a selective ET(A) receptor (ET(A)-R) antagonist in a rat model of APAE over 3 h. APAE rats developed a higher right ventricular systolic pressure (RVSP), lower mean arterial blood pressure (MABP), and had lower PaO(2). At 3 h, arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…12,20 In this regard, many studies have shown that nonselective ET-receptor antagonism or blockade of ET-1 type A (ETA) receptors attenuates the hemodynamic responses to APE. 4,5,23 Besides the fact that MMPs can modulate vascular tone, [10][11][12] our present observations that MMP-9 is activated after APE provides a potential mechanism involved in pulmonary vascular remodeling of chronic thromboembolic pul-monary hypertension. Similar to other forms of pulmonary hypertension, increased MMP activity may play a role in cell migration and in regulating the composition of extracellular matrix associated with the vascular remodeling processes.…”
Section: Discussionmentioning
confidence: 63%
“…12,20 In this regard, many studies have shown that nonselective ET-receptor antagonism or blockade of ET-1 type A (ETA) receptors attenuates the hemodynamic responses to APE. 4,5,23 Besides the fact that MMPs can modulate vascular tone, [10][11][12] our present observations that MMP-9 is activated after APE provides a potential mechanism involved in pulmonary vascular remodeling of chronic thromboembolic pul-monary hypertension. Similar to other forms of pulmonary hypertension, increased MMP activity may play a role in cell migration and in regulating the composition of extracellular matrix associated with the vascular remodeling processes.…”
Section: Discussionmentioning
confidence: 63%
“…This hypothesis is supported by previous evidence demonstrating that neutrophil MMP-9 cleave big ET-1 producing further activation of neutrophils in a positive feedback loop that promotes leukocyte -endothelial cell adhesion and neutrophil migration into inflamed tissues [12,22]. Finally, many studies have shown that nonselective ET-receptor antagonism or blockade of ET-1 type A (ETA) receptors attenuates the hemodynamic responses to APE [4,5,27].…”
Section: Time (Min) After Apementioning
confidence: 74%
“…Furthermore, elevation of plasma ET-1 and effectiveness of selective ET-1 receptor antagonist have also been shown in the experimental pulmonary air embolism model (4,35,38). Collectively, it is suggested that ET-1 may contribute to development of several forms of PE.…”
Section: Discussionmentioning
confidence: 92%